Development of Peureulak History in Video Based for Learning Social Science in Grade IV Students of 1 Peureulak East Aceh - Rosnida Rosnida; Ichwan Azhari; Wildansyah Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Peureulak's history video in social studies learning for grade 4 students at SDN 1 Peureulak, East Aceh. This type of research is research and development which refers to the development model of Borg And Gall. The results of this study indicate that: (1) Validation of material experts on the content feasibility assessment is on very good criteria (96.25%), language feasibility is in very good criteria (89%) and the feasibility of presentation is in sufficient criteria (74%). The practicality level of Peureulak's historical videos is concluded based on teacher responses and student responses; (i) Students' responses to Peureulak's historical video in the field trial amounting to 83% of students stated that the Peureulak history video was practical, (ii) The response of Peureulak's history video teacher in the field trial was 81% in the practical category. Likewise with the influence of the use of Peureulak's historical videos on student learning outcomes based on the pretest and posttest analyzed using N-Gain obtained an average gain value of 0.8 where in the high category.